PENGEMBANGAN MODEL PEMBELAJARAN BAHASA INGGRIS INDUKTIF BERBASIS LAGU KREASI - Ni Made Ratminingsih (Universitas Negeri Malang, 2014)
Abstract: Song-Based Inductive Instructional Model for English Teaching. This study aims at developing a model of English instruction in primary school utilizing created songs. This research and development adapted Gall, Gall & Borg's (2003) model. The developed product covers teaching materials, strategies, and assessment. The validation process on content reveals that the product is valid; the product quality is of good category.  The empirical field testing shows that the model is effective in improving the students' learning achievement. Responses to the questionnaire also indicate that the majority of the students are  highly motivated to study English through this song-based inductive instructional model. Keywords: inductive instruction, created songs, English teaching Abstrak: Pengembangan Model Pembelajaran Bahasa Inggris Induktif Berbasis Lagu Kreasi. Penelitian ini bertujuan mengembangkan sebuah model pembelajaran bahasa Inggris di sekolah dasar berbasis lagu kreasi. Penelitian dan pengembangan ini mengadaptasi Gall, Gall & Borg (2003). Model terdiri atas materi, strategi, dan asesmen pembelajaran. Hasil validasi isi menunjukkan bahwa produk dinilai valid, dan kualitas produk terkategori baik. Hasil uji empiris penelitian menunjukkan bahwa model yang dikembangkan efektif dalam meningkatkan hasil belajar siswa. Hasil angket juga mengindikasikan bahwa majoritas siswa memiliki motivasi yang tinggi belajar melalui model pembelajaran induktif berbasis lagu. Kata kunci: pembelajaran induktif, lagu kreasi, pembelajaran Bahasa Inggris